Design as art - Munari, Bruno (London Penguin, 2008)
Bruno Munari was among the most inspirational designers of all time, described by Picasso as 'the new Leonardo'. Munari insisted that design be beautiful, functional and accessible, and this enlightening and highly entertaining book sets out his ideas about visual, graphic and industrial design and the role it plays in the objects we use everyday. Lamps, road signs, typography, posters, children's books, advertising, cars and chairs - these are just some of the subjects to which he turns his illuminating gaze.
Design as art -- Designers and stylists : what is a designer? ; Pure and applied ; A living language ; A rose is a rose is a ; The stylists ; Mystery art -- Visual design : Character building ; The shape of words ; Poems and telegrams ; Two in one ; A language of signs and symbols? ; 12,000 different colors -- Graphic design : Poster with a central image ; Poster without end ; Children's books -- Industrial design : Micro-art ; How one lives in a traditional Japanese house ; What is bamboo? ; A spontaneous form ; A prismatic lamp ; Wear and teat ; Orange, peas and rose ; A piece of travelling sculpture ; Luxuriously appointed gentlemen's apartments ; Knives, forks, and spoons ; And that's not all ; Fancy goods -- Research design : Iris ; Growth and explosion ; Concave-convex forms ; The tetracone ; Yang-yin ; Moiré ; Direct projection ; Projections with polarized light ; The square ; The circle ; An arrow can lose its feathers but not its point ; Theoretical reconstruction of imaginary objects ; Exercises in topology, or rubber-sheet geometry ; Two fountains, nine spheres -- Appendix : the machines of my childhood (1924).
Originally published (in Italian) by Editori Laterza, 1966.
Originally published in translation by Pelican Books, c1971.
Keywords: Design -- Philosophy; Art and design